2016
DOI: 10.5603/gp.2016.0009
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome according to chorionicity in twins — a Polish multicenter study

Abstract: Objectives: The aim of the study was to analyze the perinatal outcome of twin gestations and estimate the influence of chorionicity on the outcome in a large cohort of twin pregnancies in Poland. Material and methods:A retrospective analysis of 465 twin deliveries in 6 Polish centers in 2012 was conducted. Baseline characteristics, the course of pregnancy and labor, as well as the neonatal outcome were analyzed in the study group and according to chorionicity. Results:A total of 356 twin pregnancies were dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Quality of the included studies is shown in Figure 2. In all, 97% of the studies were low risk for study selection (38/ 39), 4,14-38,40-51 10% (4/39) were low risk for comparability 28,32,40,49 and all studies were low risk for study outcome (100%). 4, One study had a medium risk of bias for study selection (3%), 39 32 studies for comparability 4,14,15,17,[20][21][22][23][24][25][26][27][29][30][31][33][34][35][36][37][38][39][41][42][43][44][45][46][47][48]50,51 and none of the studies had a medium risk of bias for outcome.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Quality of the included studies is shown in Figure 2. In all, 97% of the studies were low risk for study selection (38/ 39), 4,14-38,40-51 10% (4/39) were low risk for comparability 28,32,40,49 and all studies were low risk for study outcome (100%). 4, One study had a medium risk of bias for study selection (3%), 39 32 studies for comparability 4,14,15,17,[20][21][22][23][24][25][26][27][29][30][31][33][34][35][36][37][38][39][41][42][43][44][45][46][47][48]50,51 and none of the studies had a medium risk of bias for outcome.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…28,41 Seven of the 39 studies (18%) reported on pregnancies which are asymptomatic for preterm labour 20,22,34,38,45,50,51 whereas 31 studies reported on pregnancies which were both symptomatic and asymptomatic for preterm labour. 4,[14][15][16][17][18][19]21,23,24,[26][27][28][29][30][31][32][33][35][36][37][39][40][41][42][43][44][46][47][48][49] Seven studies (18%) reported on treatment or prophylaxis for preterm labour. 36,37,39,42,48,50,51 Around 80% (31/39) of the studies reported on both spontaneous and iatrogenic preterm birth 4,38,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Some authors reported that factors such as chorionicity, mode of delivery, type of fetal growth (discordant or symmetric), and birth mass worsen perinatal outcomes and increase the rate of neonatal complications in the second twin compared to the first one. [8][9][10] On the other hand, broad trials have been conducted which did not show the superiority of CS vs VD in terms of complications in neonates, especially in the absence of risk factors and when the first twin is in the cephalic presentation. [11][12][13] The authors of the meta-analysis from 2011, which included nearly 40,000 twin pairs, concluded that, in the absence of risk factors, VD is safer than CS for the first twin but for the second twin, the mode of delivery had no effect on perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%